ANALISIS MAKNA LIRIK DAN MELODI BUKA LANGSE SEBAGAI STRUKTUR PEMBUKA TEATER ABDUL MULUK DI DESA SEMBUBUK MUARO JAMBI - Dinda Assalia Avero Pramasheilla; Gen Dekti; Ikhsan Satria Irianto; Lusi Handayani; Sarbeni (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2025)
This study aims to reveal the meaning of the lyrics and their relationship with the melodic structure of Buka Langse as the opening segment in the traditional theater performance Abdul Muluk. The research employs a qualitative approach using a descriptive-analytical method through observation, interviews, and documentation study. The findings show that each verse of the Buka Langse lyrics carries both denotative and connotative meanings that reflect the religious, social, and moral values of the Malay Jambi community. The greetings, introduction of the play, and expressions of apology within the lyrics represent the interaction between performers and the audience. In addition to serving as a marker of the performance’s commencement and a medium for transmitting spiritual values, the lyrics also represent the cultural identity of the Sembubuk community, positioning this traditional theater as both an expressive art form and a means of preserving cultural heritage.